An investigation about the formation of N-nitrosomaprotiline under physiological conditions [Fizyolojik kosullarda N-nitrozomaprotilin olusumunun arastirilmasi] - (:unkn) unknown (My University, 1997)
In this study first N-nitroso derivative from maprotiline hydrochloride which is a therapeutic agent comprising secondary amine group in its structure, was synthesized and characterized by IR-, 1H NMR spectroscopy and Mass spectrometry and secondly the formation of N-nitrosomaprotiline under simulated stomach conditions was examined and the amount of N- nitrosomaprotiline was determined colorimetrically. Under physiological conditions the yield of N-nitrosomaprotiline was found to be 0.35%. Ascorbic acid added to the reaction medium is able to inhibit the formation of NOM up to 80.6%.
Keywords: Drug-nitrite interaction; N-nitroso compounds; N-nitrosomaprotiline